The Role of Child Rehabilitation as an Alternative to Criminal Punishment in the Child Criminal Justice System in Indonesia - Nidatunnisa Nidatunnisa; Padrisan Jamba (Sean Institute, 2026)
The juvenile criminal justice system in Indonesia is designed to provide special protection for children in conflict with the law by prioritizing the best interests of the child. One form of such protection is the implementation of rehabilitation as an alternative to punishment. Rehabilitation views children not merely as offenders, but as individuals who are still in the process of development and possess significant potential for change. This study aims to analyze the role of child rehabilitation as an alternative form of punishment within the juvenile criminal justice system in Indonesia and to examine the obstacles in its implementation. This research employs a normative legal research method using statutory and conceptual approaches, supported by relevant primary and secondary legal materials. The findings indicate that, normatively, child rehabilitation has been recognized as an alternative punishment consistent with the objectives of the juvenile criminal justice system and the principles of restorative justice. However, in practice, rehabilitation has not yet become the primary option in handling cases involving children in conflict with the law. The main obstacles include limited facilities and infrastructure, differing interpretations among law enforcement officials, and social stigma against child offenders. Therefore, strengthening the implementation of child rehabilitation is essential through a shift in punitive paradigms, enhancement of rehabilitation institutions, and active involvement of families and communities to ensure that rehabilitation functions effectively as a humane and future-oriented alternative to punishment.